SBAR Communication Role Play Method to Improve Handover Capability in Internal Patient Transfers in the Inpatient Room - Handayani, Whilis; Dwiantoro, Luky; Suryawati, Chriswardani (Indonesian Journal of Global Health Research, 2024)
Hospitals are an integral part of a social and health organization that has an important role in realizing optimal public health status. The quality of service in the hospital can be seen from the hospital's readiness to implement a patient safety culture. Patient transfer is a series of patient handover activities between nurses and fellow nurses or other health teams. Communication carried out by nurses at the time of handover has a very important role. The purpose of this study is to be able to apply nursing service management innovations, especially in the field of nursing managerial in accordance with the development of science and technology. The sampling technique in this study is a non-probability technique of purposive sampling where sampling is based on predetermined criteria. The data collection process uses interview and observation data by filling out observation sheets. The next stage of the data from the results of the questionnaire and observations was carried out a root cause analysis by assessing man, money, method, machine, material, and environment. the results of the root cause analysis with the fishbone analysis method. The research was conducted at one of the X Hospitals in Semarang, the implementation began on September 21, 2023 to October 21, 2023. The results of the assessment then analyzed using CARL showed a result of 192 which stated that the application of SBAR communication in the internal transfer of patients was less than optimal and the value of 144 showed less than optimal implementation of nursing care. Effective communication roleplay innovation is one of the effective efforts in carrying out the SBAR handover method in the internal transfer of patients in solving the problems that occur in hospital X Semarang City. Effective communication roleplay innovation can improve the ability of the head of the room and team leader in carrying out handover using the SBAR method according to standards and effective in improving communication during handover.